2017
DOI: 10.7205/milmed-d-17-00079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Readiness Training on Reserve Officers' Training Corps Freshmen Cadets

Abstract: Nine months of PRT improved APFT scores of freshmen cadets while minor effects were noted in laboratory-based performance. Given the lack of improvements in strength and power, it would be advisable to provide supplemental strength and power training. Being a large commissioning resource for the Army with greater access to equipment and resources, the time spent in ROTC may be a unique opportunity to improve and educate young commissioning officers on the benefits of proper strength and power training for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
4
12
0
2
Order By: Relevance
“…These findings may be a result of the required PT improving the PFA scores and overall fitness of the freshmen to the PFA and fitness levels of their fellow upperclassmen cadets. Recently, Oliver et al [14] investigated the effects of PT in freshman U.S. Army ROTC cadets throughout the 9-month academic year. Their results indicated that PT is effective in improving the fitness level of freshman cadets when implementing the Army PFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may be a result of the required PT improving the PFA scores and overall fitness of the freshmen to the PFA and fitness levels of their fellow upperclassmen cadets. Recently, Oliver et al [14] investigated the effects of PT in freshman U.S. Army ROTC cadets throughout the 9-month academic year. Their results indicated that PT is effective in improving the fitness level of freshman cadets when implementing the Army PFA.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical assessments of physical fitness may possess a higher degree of reliability and validity in comparison to field-based measurements [17]. While previous studies by Thomas et al [5] and Oliver et al [14] implemented both field-based (U.S. Army physical readiness test) and clinical assessments (VO 2max , 1-repetition maximum bench press, vertical jump, body fat percentage) in their studies with U.S. Army ROTC cadets, these measures served as more of a physical fitness profile regarding the cadets’ status in training than an evaluation of the validity of the field-based assessments. Future research with ROTC cadets or tactical athletes (active duty military members, firefighters, or police officers) may consider incorporating more clinical assessments in addition to field-based assessments to provide a better understanding of the individuals’ physical performance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous works indicate that the structure of the body, mainly the distribution of adipose tissue, especially the abdominal one, may be associated with the inclination to the incidence of numerous civilization diseases (Ward et al 2015). It is evident that the composition of the body is a high-lability parameter, depends on sex, but also changes with age, diet, and lifestyle as well as physical activity (Hughes et al 2002;Oliver et al 2017;Wood et al 2017). Therefore, the work tries to evaluate the relationship of body composition as a very variable factor with the quotient of the 2 nd and 4 th fingers length as a trait stabilized in the early stages of fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Об'єктивною основою цього є перенесення на боєздатність фізичних якостей, рухових навичок, біологічних властивостей організму, особливостей психіки та свідомості військовослужбовців, сформованих у процесі фізичної підготовки. Військовослужбовці з високим рівнем розвитку фізичних якостей в умовах бойових дій переважають за різними показниками військово-професійної діяльності військовослужбовців, у яких рівень цих якостей нижчий [7,9]. Завдяки високому рівню фізичної підготовленості військовослужбовці здатні долати значні фізичні, психічні навантаження, зберігати високий рівень працездатності та стресостійкості, протистояти негативним чинникам бойової діяльності та швидше відновлювати рівень боєздатності.…”
Section: науковий часопис нпу імені мп драгоманова Scientific Journal National Pedagogical Dragomanov University випуск 1 (121) 2020unclassified